Targeted Nanotherapies for the Posterior Segment of the Eye: An Integrative Review on Recent Advancements and Challenges - Gogoi, Niva R.; Marbaniang, Daphisha; Pal, Paulami; Ray, Subhabrata; Mazumder, Bhaskar (Pharmaceutical Nanotechnology, 2022)
The eye is a one-of-a-kind sensory organ with intricate anatomy and physiology. It is protected by a variety of barriers, ranging from static barriers to dynamic barriers. Although these barriers are very effective at protecting the eye from exogenous substances and external stress, they are highly compromised by various vision-impairing diseases of both the anterior and the posterior segment of the eye. Due to ocular elimination systems and intricate obstacles that selectively limit drug entry into the eye, effective drug delivery to the posterior segment of the eye (PSE) continues to be a challenge in ophthalmology. Since more than half of the most debilitating eye illnesses are thought to originate in the posterior segment (PS), understanding the physiology and clearance mechanism of the eye could help design improved formulations that could be noninvasive and intended for targeted posterior segment therapeutics. Moreover, the major drawback associated with the conventional drug delivery system to PSE is minimal therapeutic drug concentration in the desired ocular tissue and life-threatening ophthalmic complications. One possible approach that can be implemented to overcome these ocular barriers for efficient ocular therapy, non-invasive and targeted drug action to the posterior tissues is by designing nanomedicines. This review summarizes the recent non-invasive and patient compliant advances in designing nanomedicines targeting PSE. The various routes and pathways of drug administration to the ocular tissue are also summarized.
Keywords: posterior segment of the eye